Comparison of the EuroSCORE I, EuroSCORE II and STS Scales in Cardiac Surgery of High-Risk Patients with Complicated Forms of CAD - Gogayeva, O. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Before performing cardiac surgery, risk stratification is necessary in order to predict the outcome of the operation. Today, there are European risk calculators EuroSCORE I, EuroSCORE II and the scale of the American Society of Thoracic Surgeons – STS. The aim. To compare prognostic scales for high-risk patients with complicated forms of coronary artery disease (CAD). Materials and methods. Post-hoc analysis of the data obtained from 100 random high-risk patients with complicated forms of CAD who were operated and discharged from Amosov National Institute in the period from 2009 to 2019. For all patients, risk factors were analyzed and calculated using three risk scales. Results. In addition to the initial severity of cardiovascular disease, the patients of the study group had comor-bidities like diabetes mellitus (23%), obesity (33%), and chronic kidney disease (34%), atherosclerosis of brachio-cephalic arteries (57%), chronic obstructive pulmonary disease (78%), a history of cerebrovascular accident (9%) etc. The predicted operative mortality was 19.2% according to the ES I scale, 8.6% according to the ES II, and 2.6% according to the STS scale, while mortality in the study group was 0%. An analysis of the ten-year experience of National Amosov Institute in the surgical treatment of CAD in more than 15,000 patients showed 0.9% mortality in complicated forms of high-risk CAD, which is significantly less than the forecast according to all the three scales. The ES I scale is characterized by a significant overestimation of mortality rates, the STS scale is cumbersome, time consuming, predicts 9 indicators that are not statistically significant in comparison with real practice. The most modern and convenient to use, but though not 100% reliable, is the ES II scale. The scales are necessary to stratify the risk and to understand the severity of the patient’s condition. It should be kept in mind that, in addition to comorbidities as well as cardiac and non-cardiac factors, the result of surgical intervention is influenced by the coordinated work of the Heart Team consisting of a cardiologist, interventional cardiologist, functional diagnostics doctor, cardiac surgeon, anesthesiologist and resuscitator.